2013
DOI: 10.1063/1.4812712
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potential fluctuations on shot noise suppression in mesoscopic cavities

Abstract: We perform a numerical investigation of the effect of the disorder associated with randomly located impurities on shot noise in mesoscopic cavities. We show that such a disorder becomes dominant in determining the noise behavior when the amplitude of the potential fluctuations is comparable to the value of the Fermi energy and for a large enough density of impurities. In contrast to existing conjectures, random potential fluctuations are shown not to contribute to achieving the chaotic regime whose signature i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…6, where the Fano factor for an 8 µm wide and 5 µm long cavity with randomly located hard-wall square 50 × 50 nm 2 scatterers and 800 nm wide constrictions is reported as a function of their number (analogous results can be obtained with realistic disorder profiles, see Ref. [23]). As the number of scatterers is increased, we notice that the Fano factor raises above 1/4, without even a hint of a plateau, then reaches 1/3, with a plateau, and finally rises well above such level.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…6, where the Fano factor for an 8 µm wide and 5 µm long cavity with randomly located hard-wall square 50 × 50 nm 2 scatterers and 800 nm wide constrictions is reported as a function of their number (analogous results can be obtained with realistic disorder profiles, see Ref. [23]). As the number of scatterers is increased, we notice that the Fano factor raises above 1/4, without even a hint of a plateau, then reaches 1/3, with a plateau, and finally rises well above such level.…”
Section: Introductionmentioning
confidence: 75%
“…Thus it is suggested that disorder helps in reaching the limit in which fully chaotic transport appears, but, in reality, this is just a consequence of the relatively small disorder amplitude that was considered in such studies. Indeed, we have shown [23] that as the amplitude of disorder in the cavity is increased, it contributes to a diffusive behavior typical of disordered conductors with a Fano factor greater than 1/4 (1/3 for the particular case in which all requirements for fully diffusive transport are satisfied, a situation, however, not so common in most mesoscopic conductors [34]), prevailing over any specific cavity effect. This can be clearly seen in Fig.…”
Section: Introductionmentioning
confidence: 95%
“…The potential disorder has been approximately represented with a sum of Gaussian functions randomly distributed over the flake (see (2)), with concentration n imp =5×10 11 cm −2 , random amplitude uniformly distributed between −120 and 120 meV and half-width at half-maximum equal to 5 nm. These values have been obtained from the equations (2) to (7), considering E F = 50 meV, d = 1 nm and ε r = 2.5. In Fig.…”
Section: Numerical Results and Comparison With Previous Approachesmentioning
confidence: 99%
“…Since the end of the past century, a significant research effort has been spent on the proposal, analysis and fabrication of novel devices at the nanoscale, based on new materials, geometries, technological solutions or operating principles. For example, the fabrication of nanodevices based on III-V heterostructures, characterised by a high-mobility two-dimensional (2D) channel, has allowed to study transport and noise [1][2][3][4][5][6][7] in the ballistic regime. Moreover, devices based on new geometries and operating principles (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such fluctuations derive from underlying microscopic phenomena and in sensors they may limit the achievable sensitivity or, as in the case of fluctuationenhanced sensing [1], contribute to the improvement of sensor performance, in particular in terms of selectivity. Several forms of random electrical fluctuations may exist in electronic devices: shot noise, thermal noise, generationrecombination noise, burst noise, and 1/f (flicker) noise, just to cite the main ones [2][3][4][5][6][7][8][9]. They differ for their physical origin and for the dependence of their power spectral density on the physical parameters characterizing the device operation, such as temperature, frequency, bias current, charge density, and material resistivity.…”
Section: Introductionmentioning
confidence: 99%